ANALISIS PENGARUH FASILITAS DAN HARGA TERHADAP LOYALITAS PENGHUNI RUMAH KOS-KOSAN (STUDI KASUS: RIDHO RIZKY DI PERUMAHAN DARUSSALAM) - Suci Rahmadani; Sandra Dewi (Jurnal Ekonomi dan Bisnis, 2023)
This study was conducted to analyze and determine the effect of facilities and prices on customer loyalty of boarding house service businesses. Using quantitative descriptive methods, primary and secondary data as data sources. Using the total sampling technique method, so that all boarding house residents as a population are used as samples. For data collection, observation and questionnaire distribution were carried out. Data processing techniques use quality tests, classical assumption tests and hypothesis tests. to analyze data using descriptive analysis and multiple linear regression analysis using the SPSS 26 program. The results obtained from multiple linear regression analysis Y = -0.153 + 0.576X1 + 0.412X2. This is evidenced by the t test, which shows that the variable value of facilities has a significant positive influence on the loyalty of boarding house residents, with the t-value calculated > t table which is 11.725 > 1.998 so that it can be declared Ha accepted. The price variable has a significant positive influence on loyalty which can be shown by the value of t calculated > t table which is 11.309 > 1.778, it can be stated that Ha is received. The test shows that facilities and prices partially have a significant effect on loyalty with the value of f calculated > f table which is 88.372 > 3.14. With the value of the coefficient of determination, it shows that the effect of facilities and prices on the loyalty of boarding house residents is 0.701. From the findings conducted by statistical testing of facilities and prices on loyalty has a strong contribution indication of 70.1% which affects loyalty.